2021
DOI: 10.1108/jic-05-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between intellectual capital and profitability with interaction effects: panel data evidence from the Indian healthcare industry

Abstract: PurposeThis study seeks to understand the nexus between intellectual capital and profitability of healthcare firms in India with interaction effects.Design/methodology/approachRelevant data were extracted from the Centre for Monitoring Indian Economy (CMIE)'s Prowess database for a period of ten years 2009–2018 for a sample of 84 selected firms from the healthcare industry. This study uses value added intellectual coefficient (VAIC) and modified value added intellectual coefficient (MVAIC) as a measure of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 90 publications
4
62
1
Order By: Relevance
“…Several studies have reported the evidence of significant and positive relationship between intellectual capital and profitability (e.g. Vishnu et al, 2014;Nimtrakoon, 2015;Dzenopoljac et al, 2016;Scafarto et al, 2016;Nawaz et al, 2017;Ozkan et al, 2017;Tiwari et al, 2018;Tiwari, 2020). Thus, the first hypothesis is as follows:…”
Section: Hypotheses Developmentmentioning
confidence: 95%
See 3 more Smart Citations
“…Several studies have reported the evidence of significant and positive relationship between intellectual capital and profitability (e.g. Vishnu et al, 2014;Nimtrakoon, 2015;Dzenopoljac et al, 2016;Scafarto et al, 2016;Nawaz et al, 2017;Ozkan et al, 2017;Tiwari et al, 2018;Tiwari, 2020). Thus, the first hypothesis is as follows:…”
Section: Hypotheses Developmentmentioning
confidence: 95%
“…Many research papers have provided evidence that human capital supports structural capital, relational capital, which in turn have a direct impact on firm performance (e.g. Huang and Hsueh, 2007;Hsu and Fang, 2009;Leitner;2011;Gonzalez-Loureiro and Dorrego, 2012;Scafarto et al, 2016;Sardo et al, 2018;Tiwari et al, 2018;Tiwari, 2020). Therefore, this study attempts to make a contribution by measuring the moderating role of human capital in the relationship between intellectual capital and firm performance.…”
Section: Intellectual Capital and Firm Performancementioning
confidence: 97%
See 2 more Smart Citations
“…As a result, a thorough understanding of the components of intellectual capital coefficients is critical for an organization's success. It may hold the key to achieving the desired levels of intellectual Capital (Tiwari, 2020). Moreover, Laing, Dunn, and Hughes-Lucas (2010) specified that the MVAIC model that combines the three IC components of HCE, SCE, and RCE is a valid evaluation instrument and capable of imparting discrete values IC.…”
Section: Empirical Analysismentioning
confidence: 99%